2019
DOI: 10.2147/ppa.s196103
|View full text |Cite
|
Sign up to set email alerts
|

<p>Health-related quality-of-life and treatment satisfaction of individuals with hemophilia A treated with turoctocog alfa pegol (N8-GP): a new recombinant extended half-life FVIII</p>

Abstract: Background Prophylactic treatment regimens lead to improvements in health-related quality-of-life (HRQoL) among individuals with hemophilia. Turoctocog alfa pegol (N8-GP) provides the benefit of extending the duration of protection from bleeding and reducing the number of injections, which is expected to impact HRQoL and treatment satisfaction (TS). Aim To investigate the HRQoL and TS of patients with severe hemophilia A from two phase III trials evaluating the safety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 22 publications
(35 reference statements)
4
37
0
2
Order By: Relevance
“…Others have also shown significant improvements in HRQoL when boys with high rates of target joints and/or high ABRs switch to an EHL FVIII. Kearney and colleagues showed that boys (n = 68) and their parents reported improvements in most domains of the Haemo‐QoL (a Haemophilia‐specific HRQoL questionnaire) when switching from a SHL FVIII to a glycopegylated EHL FVIII (N8‐GP; Novo Nordisk, Bagsvaerd , Denmark) as part of the Pathfinder‐5 study . However, a considerable proportion (15/68; 22%) of the boys in the study had target joints at baseline prior to switching to the EHL FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also shown significant improvements in HRQoL when boys with high rates of target joints and/or high ABRs switch to an EHL FVIII. Kearney and colleagues showed that boys (n = 68) and their parents reported improvements in most domains of the Haemo‐QoL (a Haemophilia‐specific HRQoL questionnaire) when switching from a SHL FVIII to a glycopegylated EHL FVIII (N8‐GP; Novo Nordisk, Bagsvaerd , Denmark) as part of the Pathfinder‐5 study . However, a considerable proportion (15/68; 22%) of the boys in the study had target joints at baseline prior to switching to the EHL FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…During the extension phase, PRO questionnaires were collected annually. Detailed methods of the questionnaires used and main phase results have been previously published 5 . In short, aged‐based versions of the Haemo‐QoL questionnaires were distributed to patients in the age groups 4‐7 years (Haemo‐QoL I) and 8‐12 years (Haemo‐QoL II) and their parents.…”
Section: Methodsmentioning
confidence: 99%
“…The pathfinder5 trial comprised a main phase and an extension phase. Results from the main phase, which encompassed 50 exposure days (EDs) of twice‐weekly 60 IU/kg N8‐GP treatment, showed a median annualized bleeding rate (ABR) of 1.95, with 42.6% of patients experiencing no bleeding episodes, 4 maintenance or improvement in health‐related quality of life (QoL) measure, 5 and good tolerability 4 . Following completion of the main phase, patients could continue prophylactic treatment with N8‐GP in an extension phase, totaling up to 5.5 years of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Haemophilia A (HA), a congenital bleeding disorder characterized by deficiency of coagulation protein factor (F)VIII, has a negative impact on the health-related quality of life (HRQoL) of affected people. [1][2][3] A clinical hallmark of severe HA is recurrent spontaneous bleeds, particularly into joints, and a substantial corresponding impact on physical health and HRQoL. [4][5][6][7][8] Approximately 30% of previously untreated persons with haemophilia A (PwHA) develop one of the most challenging complications of haemophilia treatment: neutralizing alloantibodies (inhibitors) against FVIII, [9][10][11] preventing effective FVIII prophylaxis.…”
Section: Introductionmentioning
confidence: 99%